6 Ga. Code 234-36 (1915) - (:unkn) unknown (My University, 1910)
Penal Code, Article 3, Carrying pistols without license, § 348(a)-(d): Prohibited the carry of any pistol or revolver without first obtaining a license from respective county in which the party resides. Subsections dictated how licenses were obtained and the cost of obtaining such licenses. Violators guilty of a misdemeanor.
Keywords: CARRY